Markov chain-based evaluation of the certificate status validations in hybrid MANETs. (15th February 2017) - Masdari, Mohammad
Abstract: Mobile ad hoc networks (MANETs) are vulnerable to various security attacks conducted by the malicious nodes and attackers. To defend against the attackers, their public key certificates should be revoked by certificate authority. Thus, each MANET node before conducting any secure communications, should check the status of communicating parties' certificates. Inconsistency of the certificate status information is one of the critical problems which reduce the correctness and effectiveness of the whole certificate validation process. In this paper, we conduct a Markov-chain based analysis and evaluation of the OCSP-based certificate validations in the hybrid MANETs. In particular, we focus on the ADOPT and PS-ADOPT protocols and present four absorbing Markov-chain models, three for online states whose OCSP responder is available to the MANET and the other to support offline cases where MANET may be disconnected from the OCSP responder occasionally. Finally, the results of absorbing Markov models are verified by the extensive simulations of the ADOPT and PS-ADOPT protocols in the OMNeT++ simulator.